The Effectiveness of Recreation Progam on Self-Esteem of Aging in the Elderly Club of Danmeakhmmon Subdistrict, Uttaradit Province, Thailand (Unnes Journal of Public Health, 2020)
This research aims to study and compare the effects of recreation on aging and self-esteem of the elderly at the Elderly Club of the Danmeakhammon sub-district in the Uttaradit Province, Thailand. This was a quasi-experimental study with one-group pretest-posttest design. The population is the 458 elders from the age of about 60-69 years old who is a member of the elderly club, Dan Mae Khamman Sub-district, Uttaradit Province, Thailand. The respondents were fifty people between sixty to sixty-nine years old from the Elderly Club in the Danmeakhammon sub-district, Uttaradit Province, Thailand. The respondents were selected purposively with inclusion condition of passing some preliminary medical examinations. The exclusion condition was not willing to participate in recreational programs as treatment. The recreational program was held twice a week for 8 weeks (totally 16 times). Self-esteem evaluation form with Coopersmith Concept and all tools for holding recreational program were listed as instruments of this study. Data were analyzed with paired t-test. The result of the study was that after participating the recreational program, the respondents significantly had better self-esteem (p = 0.0001).